"Security Here is Not Safe": Violence, Punishment, and Space in the Contemporary US Penitentiary. (June 2013) - Morin, Karen M
The US penitentiary at Lewisburg, Pennsylvania, was retrofitted in 2008 to offer the country's first federal Special Management Unit (SMU) program of its kind. This model SMU is designed for federal inmates from around the country identified as the most intractably troublesome, and features double-celling of inmates in tiny spaces, in 23-hour or 24-hour a day lockdown, requiring them to pass through a two-year program of readjustment. These spatial tactics, and the philosophy of punishment underlying them, contrast with the modern reform ideals upon which the prison was designed and built in 1932. The SMU represents the latest punitive phase in American penology, one that neither simply eliminates men as in the premodern spectacle, nor creates the docile, rehabilitated bodies of the modern panopticon; rather, it is a late-modern structure that produces only fear, terror, violence, and death. This SMU represents the latest of the late-modern prisons, similar to other supermax facilities in the US but offering its own unique system of punishment as well. While the prison exists within the system of American law and jurisprudence, it also manifests features of Agamben's lawless, camp-like space that emerges during a state of exception, exempt from outside scrutiny with inmate treatment typically beyond the scope of the law.